Комунікативна культура в епоху інформатизації - Вракіна, К. П. (ХНУРЕ, 2020)
The article is devoted to communication in today’s culture which is heterogeneous and has many delusions. It deals with communication as a phenomenon that operates on two basic levels: individual and collective. Different peculiarities of functioning of communication are suggested here. Also some features of the information society are described in this article. For example resolved problem of information crisis, provided the priority of information and information as the main form of development. The main communicative problem is that people are not ready for informatization.
Keywords: філософія; комунікативна культура